Efficacy of Open Anderson-Hynes Pyleloplasty in Congenital Unilateral Uretero-Pelvic Junction Obstruction in Term of GFR in Children - Faiz Ur Rahman, Saif Ud Din, Zia Ullah, Muhammad Ibrahim Shuja, Ahmad Ali, Jehangir Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the efficacy of Open Anderson-Hynes pyeloplasty in unilateral congenital UPJO in terms of GFR, free drainage of urine from the pelvis to the ureter and symptomatic improvement in children aged 5 to 15 years. Keywords: Pyeloplasty, Anderson-Hynes, Pediatric Pyeloplasty, Uretero-Pelvic Junction Obstruction